COMPARISON OF INTRATHECAL NALBUPHINE VERSUS DEXMEDETOMIDINE WITH LEVOBUPIVACAINE FOR POST- OPERATIVE ANALGESIA IN CAESAREAN SECTION: A PROSPECTIVE STUDY. - Dr. Darshika M. Rathva; Dr. Bhumika A. Raval; Dr. Sonali P. Prajapati; Dr. Umang G. Thakkar; Dr. Geeta P. Parikh; Dr. Beena K. Parikh (Journal of Population Therapeutics and Clinical Pharmacology, 2024)
Background and Objectives: Various drugs have been used as an adjuvant with local anesthetics, to prolong the duration of spinal analgesia of single shot technique. This study aims at investigating and comparing the effects of intrathecal nalbuphine and dexmedetomidine as adjuvants to hyperbaric levobupivacaine in subarachnoid block. Materials and Methods: 60 parturients undergoing elective Lower Segment Cesarean Section were allocated into 2 groups of 30 each to receive intrathecal administration of 10 mg of 0.5% hyperbaric Levobupivacaine with either 1 mg of Nalbuphine (Group N) or Dexmedetomidine 5µg (Group D).Characteristics of spinal anesthesia in terms of sensory analgesia and motor blockade, along with hemodynamic parameters and adverse effects, if any, were assessed. Data obtained was compiled and statistically analyzed with appropriate tests. Results: Onset of sensory and motor blocks was faster in Group D (2.13±0.20 and 2.32±0.18 min) compared to Group N (4.08±0.16 and 5.37±0.22 min). Total duration of effective analgesia and total duration of motor block were significantly prolonged in Group D (469.2±31.8 and 217.3±20.65 min) compared to Group N (294±17.4 and 119.8±15.26 min). There was no significant difference in the hemodynamic parameters and adverse effects between both the groups. Conclusion: The intrathecal combination of 5µg dexmedetomidine and 0.5% hyperbaric levobupivacaine provides prolonged sensory and motor blockade with enhanced perioperative analgesia compared to nalbuphine 1mg.